AlUla, the pearl of the Saudi desert - United Nations Educational, Scientific; Cultural Organization; Anuliina Savolainen (The UNESCO Courier, 2025)
The AlUla oasis in Saudi Arabia’s desert heart has long been a wellguarded archaeological secret. Today, layer by layer, the millenniaold history of this ancient crossroads of cultures – a strategic stop on the Incense Route that linked the Arabian Peninsula to the great civilizations of East and West – is being unveiled.